2018
DOI: 10.1002/adfm.201706403
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Quasi‐3D Nanocomposite: A Novel p‐Type Hole Transport Layer for High Performance Inverted Organic Solar Cells

Abstract: Hole transport layer (HTL) plays a critical role for achieving high performance solution-processed optoelectronics including organic electronics. For organic solar cells (OSCs), the inverted structure has been widely adopted to achieve prolonged stability. However, there are limited studies of p-type effective HTL on top of the organic active layer (hereafter named as top HTL) for inverted OSCs. Currently, p-type top HTLs are mainly 2D materials, which have an intrinsic vertical conduction limitation and are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…This is because of the similar thicknesses (≈100 nm) of the active layer films atop different CILs. Since optical absorption directly determines the efficiency of exciton generation within the active layer, the comparable optical absorptions of the active layer films atop different CILs is consistent with the slight change of the J sc value obtained for their corresponding devices, as confirmed further by the slight fluctuations of their external quantum efficiency (EQE) responses as well as the integrated J sc values (Figure b, see also Table S4, Supporting Information).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This is because of the similar thicknesses (≈100 nm) of the active layer films atop different CILs. Since optical absorption directly determines the efficiency of exciton generation within the active layer, the comparable optical absorptions of the active layer films atop different CILs is consistent with the slight change of the J sc value obtained for their corresponding devices, as confirmed further by the slight fluctuations of their external quantum efficiency (EQE) responses as well as the integrated J sc values (Figure b, see also Table S4, Supporting Information).…”
Section: Resultssupporting
confidence: 75%
“…Polymer solar cells (PSCs) have been attracting considerable attention as a promising renewable energy owing to their advantages of solution‐processability, high‐flexibility, light‐weight, and low‐cost . The state‐of‐the‐art PSC devices are typically constructed by the bulk heterojunction (BHJ) structure with the active layer comprised of low‐bandgap conjugated polymer donors and fullerene/non‐fullerene acceptors, and ever‐growing power conversion efficiency (PCE) exceeding 14% has now been achieved on the basis of not only developing novel active materials but also interface engineering strategy .…”
Section: Introductionmentioning
confidence: 99%
“…They showed this improvement due to a higher conductivity and W F of F‐rGO HTL. Similarly, Cheng et al [ 296 ] demonstrated the self‐assembled quasi‐3D GO:NiO x composite as a HTL in an inverted OSC. The remarkable improvement in conductivity led to a high PCE of 12.13% (average PCE was 11.45%), which was at that time the highest reported value for inverted OSCs.…”
Section: Graphene Oxide and Reduced Graphene Oxidementioning
confidence: 96%
“…[3,4,29,49] The donors with deep highest occupied molecular orbital (HOMO) levels, in particular, are incorporated to achieve a high open circuit voltage (V OC ) in NFAs-based inverted structure OSCs. [54][55][56] Furthermore, because a vacuum process is required for efficient modulation of OSCs, productivity decreases. [50][51][52][53] When the BHJ layer is incorporated into an inverted structure OSCs through a solution process, the introduction of an appropriate buffer layer between the BHJ layer and the electrode is necessary to improve the interfacial electronic properties.…”
Section: Introductionmentioning
confidence: 99%